Análise da (auto) sustentabilidade do Perímetro Irrigado Baixo Acaraú: Um estudo de caso - Oliveira, Josiane Aparecida de Lima (2008)
All across the national territory a preoccupation with the insufficiency of the hydric resources can be noticed, such resources become scarcer as the population, industry and agriculture grows. This issue is even more complicated in the Brazilian semi arid, because there is the interference of the climate factors, such as droughts and irregular rain distribution that compromise the water availability. The use of irrigation becomes essential for the individuals to perform agricultural activities in such regions, although those activities are the ones that waste water the most. Irrigation methods that allow the greatest use of this precious liquid should be adopted. With the objective of giving the cropper ways to produce and a life improvement and to generate both local and regional development, arise irrigation programs implanted by the Government through the National Department of Works Against the Drought (DNOCS), such as the Baixo Acaraú Irrigation Perimeter project. However, the execution of those projects need to be evaluated they are a large opportunity cost for society. This current research will analyze the (auto) sustainability of the Baixo Acaraú Irrigation Perimeter, evaluating economical and financial matters, social, environmental, economical and institutional dimensions through a group of sustainability indexes capable of providing an understanding of the reality of the region, in addition to observing the characteristics of this perimeter’s irrigators and their integration towards sustainable development. The methodological procedure adopted started with the gathering of the primary data, which were treated and organized. Hereinafter, were built the levels of sustainability and the individual sustainability indexes for the social, environmental, economical and institutional dimensions.The resulting indexes from this studies are presented and the results indicate that the sustainability in the Baixo Acaraú Irrigation Perimeter can be questioned, once the sustainability index shows a medium or poor degree, which indicates that this activities has not translated itself into better life conditions and development to the local population yet.